Advertisement Remove all ads

Solve `X^2-(Sqrt3+1)X+Sqrt3=0` - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads

Solve `x^2-(sqrt3+1)x+sqrt3=0`

Advertisement Remove all ads

Solution

`x^2-(sqrt3+1)x+sqrt3=0` 

⇒ `x^2-sqrt3x-x+sqrt3=0` 

⇒`x(x-sqrt3)-1(x-sqrt3)=0` 

⇒` (x-sqrt3) (x-1)=0` 

⇒`x-sqrt3=0  or  x-1=0` 

⇒` x=sqrt3  or  x=1` 

Hence, `1 and sqrt3` are the roots of the given equation.  

Concept: Application of Quadratic Equation
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RS Aggarwal Secondary School Class 10 Maths
Chapter 10 Quadratic Equations
Q 46

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×